Hearing Function, Degeneration, and Disease: Spotlight on the Stria Vascularis - Thulasiram, Matsya R; Ogier, Jacqueline M; Dabdoub, Alain (Frontiers in Cell and Developmental Biology, 2022)
The stria vascularis (SV) is a highly vascularized tissue lining the lateral wall of the cochlea. The SV maintains cochlear fluid homeostasis, generating the endocochlear potential that is required for sound transduction. In addition, the SV acts as an important blood-labyrinth barrier, tightly regulating the passage of molecules from the blood into the cochlea. A healthy SV is therefore vital for hearing function. Degeneration of the SV is a leading cause of age-related hearing loss, and has been associated with several hearing disorders, including Norrie disease, Meniere’s disease, Alport syndrome, Waardenburg syndrome, and cytomegalovirus-induced hearing loss. Despite the SV’s important role in hearing, there is still much that remains to be discovered, including cell-specific function within the SV, mechanisms of SV degeneration, and potential protective or regenerative therapies. In this review, we discuss recent discoveries elucidating the molecular regulatory networks of SV function, mechanisms underlying degeneration of the SV, and otoprotective strategies for preventing drug-induced SV damage. We also highlight recent clinical developments for treating SV-related hearing loss and discuss future research trajectories in the field.